The virtual Haydn : paradox of a twenty-first century keyboardist - Beghin, Tom, 1967- (University of Chicago Press, 2015)
Haydn's music has been performed continuously for more than 200 years. But what do we play, and what do we listen to, when it comes to Haydn? Can we still appreciate the rich rhetorical nuances of this music, which from its earliest days was meant to be played by professionals and amateurs alike? Tom Beghin - himself a professional keyboard player - delves deeply into 18th-century history and musicology to help us hear a properly complex Haydn. Unusually for a scholarly work, the book is presented in the first person, as Beghin takes us on what is clearly a very personal journey into the past.